1117 Managing Cosmetic Surgery Complications: A Retrospective Service Evaluation. (12th October 2021) - Luck, J; Strachan, E; Piggott, B; Saour, S
Abstract: Aim: The cosmetic surgery industry continues to grow, both within the UK and internationally. There is a perception that the NHS is often left to deal with the complications of these procedures, particularly those performed abroad. This study aimed to evaluate the burden of cosmetic surgery complications on a tertiary London plastics service with an appraisal of the financial costs incurred. Method: This one-year retrospective service evaluation included all emergent referrals following cosmetic surgical interventions in the UK private sector and abroad. Outpatient referrals and planned revisional procedures were excluded. Financial costs were based upon current Clinical Commissioning Group tariffs. Results: In total, 14 patients were included (seven from the UK and seven from Europe or North Africa). Remote telemedicine advice was provided for six patients; eight patients required admission. All eight admissions were female with an average age of 42.6 years. The most common complication was infection (75%) with an average length of stay of 2.3 nights. These eight patients required six trips to theatre, two CT scans and 37 outpatient visits. The median tariff per patient was £1, 510 (range £242 to £5, 196), leading to an overall reimbursement of £16, 471. The majority of these costs were generated during inpatient admissions (£12, 855) with a lesser contribution from outpatient episodes (£3, 616). Conclusions: This project provides an overview of the impact of managing emergent complications following cosmetic surgery, both in terms of service activity and financial cost. A long-term, prospective service evaluation of both elective and emergency referrals based upon patient-level costing data is now underway.